Numerical modeling of solid particles reduction in water clarifiers using Lattice Boltzmann method - E. Jaiuan; Y. Khunatorn (Alexandria Engineering Journal)
Suspended solids in water are detrimental to power plant production. Statistical data from the field turbidity monitoring states different solid particle reduction performance between two existing solid contact clarifiers. This study compares their turbidity reduction efficiencies and discusses treatment characteristics of these clarifiers. The clarifiers feature circular basins with a dual layer of baffles and different internal mixing agitation. The first clarifier (CLR47) has the inner baffle as a truncated polygon with a lateral inlet. The second clarifier (CLR89) has a 30-degree tangential inlet attached to a small circular inner baffle. The Lattice Boltzmann Method (LBM) computational method was employed for fluid flow computation. Particles with 13 different diameter sizes ranged from 20 μm to 850 μm were accounted for suspended solid modeling via discrete phase model (DPM). The numerical model presents the overall solid settling efficiency as 46 % and 78 % for CLR47 and CLR89 respectively. The low recirculation within the mixing region and effluent high contamination of 20 μm size class particles of design CLR89 were noticed. While the CLR47 model has greater turbidity reduction despite greater maintain mixing efficiency for a higher flocculation rate expectation.